- Inspiring High Performance: The Role Of Transformational Leadership And Organisational Commitment: - - Agung, Suranata; Riana, I (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
In order to evaluate the social exchange hypothesis, this study will examine how transformational leadership affects employee performance and organizational commitment. A quantitative technique was used in the study, which involved 77 Civil Servants (PNS) and was carried out in the Ministry of Industry located in Denpasar, Surabaya and Medan. The entire population served as the study sample in this non-probability sampling strategy, which used a saturated sample. Structural Equation Modelling (SEM) with a Partial Least Square (PLS) technique was used to analyse the data. The findings demonstrate that employee performance and organizational commitment are positively and significantly impacted by transformational leadership. In a similar vein, employee performance is positively and significantly impacted by organizational commitment. Additional research suggests that a key mediator in this association is organizational commitment. The results of this study imply that leaders who are inspirational in all facets of organizational life might increase their subordinates' sense of commitment to and engagement with the company, which will maximize their performance contributions..